The Economic-Environmental model PANTA RHEI and it's Application - Bernd Meyer (Gesellschaft für Wirtschaftliche Strukturforschung (GWS), 2005)
The global dimension of environmental problems stresses the need of an internationally linked environmental environmental policy. The example of climate change policy shows, that environmental policy has to be a subject of a globally oriented international policy formulating operational targets that allow for global sustainable development in the environmental, economic and social dimension. Further, a set of policy instruments hast to be installed, that will enable to reach global sustainability. Already from a political point of view of a single country the task seems to be huge, and there are many sceptical voices, whether the big political bargaining process could ever converge. A necessary but by no means sufficient condition for this is the solution of a big information problem: What does sustainable development for the future? How are the relations between the targets? What do we know about the interdependencies between the environment, the economic and the social development in the different countries? How do the different instruments affect nature and the paths of economic and social development? How is the efficiency of these instruments?
Keywords: O13; 330; PANTA RHEI; global